Molecular Prevalence of Anaplasma marginale and Ehrlichia in Domestic Large Ruminants and Rhipicephalus (Boophilus) microplus Ticks From Southern Luzon, Philippines - Galay, Remil L.; Llaneta, Carina R.; Monreal, Maria Karla Faye B.; Armero, Antero L.; Baluyut, Arianne Bel D.; Regino, Czarina Marie F.; Sandalo, Kristina Andrea C.; Divina, Billy P.; Talactac, Melbourne R.; Tapawan, Lennox P.; Mojares, Maarten Czar L.; Alvarez, Cherry R.; et al. (Frontiers in Veterinary Science, 2021)
Anaplasmosis and ehrlichiosis are tick-borne rickettsial diseases that cause significant economic losses in the livestock industry worldwide. Although bovine anaplasmosis is known to be endemic in the Philippines, epidemiological data is fragmented. Moreover, little is known about bovine ehrlichiosis in the country. In this study, the prevalence of Anaplasma marginale and Ehrlichia in cattle and water buffalo from provinces in the southern part of Luzon, Philippines, was investigated through PCR. Blood samples from 620 animals comprised of 512 cattle and 108 water buffalo and 195 tick samples were subjected to nested PCR targeting the groESL gene of Anaplasmataceae. Positive samples were further subjected to another nested PCR and conventional PCR to amplify the A. marginale groEL gene and the Ehrlichia dsbA gene, respectively. Selected A. marginale-positive samples were also subjected to nested PCR targeting the msp5 gene. Regardless of the animal host, the overall prevalence in blood samples obtained was 51.9% for Anaplasmataceae, 43% for A. marginale, and 1.1% for Ehrlichia. No water buffalo were positive for Ehrlichia. Meanwhile, 15.9%, 6.7%, and 2% of the tick samples, all morphologically identified as Rhipicephalus (Boophilus) microplus, were positive for Anaplasmataceae, A. marginale, and Ehrlichia, respectively. Sequence analysis of selected A. marginale msp5 amplicons showed that the isolates from the region share 94–98% identity to reported A. marginale from other countries. The phylogenetic tree showed clustering of isolates in the region and a close relationship with A. marginale isolates from other countries. Sequences of Ehrlichia amplicons from cattle and ticks were 97–100% similar to reported Ehrlichia minasensis isolates. This study showed the high prevalence of A. marginale in Luzon, Philippines, and provided the first molecular evidence of E. minasensis in the country.